2019
DOI: 10.11152/mu-1667
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac left heart morphology and function in newborns with intrauterine growth restriction: relevance for long-term assessment

Abstract: Aim: To asses the cardiac morphology and functional changes specific for newborns from intrauterine growth restriction (IUGR) pregnancies.Material and method: A cohort of IUGR infants were evaluated by serial echocardiographies at delivery and at the first and six months follow-ups. IUGR newborn delivery status was compared to that of newborns in the control group according to gestational age (AGA).Results: Left heart measurements were significantly lower in IUGR newborns compared to AGA babies. Left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…We found shorter length of the left ventricle both in Early-FGR compared to Non-FGR and Early-FGR compared with Late-FGR, which is in accordance with other studies [14,31]. Several studies support our ndings that both term and premature FGR neonates had smaller diameter of the left ventricle [14,[31][32][33]. Most studies have examined mainly the left ventricle, while Patey et al [14] also studied the right ventricle in their term FGR group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found shorter length of the left ventricle both in Early-FGR compared to Non-FGR and Early-FGR compared with Late-FGR, which is in accordance with other studies [14,31]. Several studies support our ndings that both term and premature FGR neonates had smaller diameter of the left ventricle [14,[31][32][33]. Most studies have examined mainly the left ventricle, while Patey et al [14] also studied the right ventricle in their term FGR group.…”
Section: Discussionsupporting
confidence: 91%
“…Cohen et al [35] found no difference in left ventricle wall thickness on day one when adjusting for body surface area, and Ciccone et al [37] found that the differences in diameter in interventricular septum and left ventricular posterior wall disappeared when normalized for body surface area in both term and premature Non-FGR neonates. Some studies report thinner ventricle septum in FGR [32,33], whereas others report opposite ndings [13,31]. Differences in study design and inclusion criteria might explain these differences.…”
Section: Discussionmentioning
confidence: 97%
“…As expected, in those with cerebral haemorrhage, brain oxygenation was lower. Brain injury in premature infants appears as a complex association of primary diseases and secondary maturational and trophic disturbances, rather than as the result of a single agent [ 22 , 23 , 24 , 25 ]. Previously, relationships between the severity of GMHIVH or PVHI and cerebral oxygenation were found [ 22 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the use of 3D imaging and color Doppler in fetal cerebral and cardiac evaluation is already well established [ 9 ], a rather recent application in fetal ultrasound diagnosis brings promising new input for assessment of surgical approach in ovarian cysts larger than 5 cm [ 8 ].…”
Section: Introductionmentioning
confidence: 99%